Socioeconomic and environmental characterization of the Igarapé da Prata watershed, Capitão Poço, State of Pará, Brazil (Research, Society and Development, 2020)
The objective of this research was to analyze the socioeconomic and environmental characteristics of the Prata river watershed which is located in Capitão Poço city, located in the middle region Northeast Pará, in order to understand the dynamics of the relationship in this area. For the realization of socio-economic and environmental assessment were obtained secondary data available in the Single Registry for Social Programs of the Federal Government of the Ministry of Social Development and Agrarian (MDS). The cartographic databases used with information on the use and occupation were the TerraClass project (2008; 2010; 2012) developed by INPE in partnership with EMBRAPA. It could be observed that the BHIP over the years had its highly modified natural vegetation which characterizes it as a pretty anthropic areas, with a heavy use of soil by agricultural practices. From the analysis of secondary data in the Single Registry, you can pay attention to the  Capitão Poço city and consequently the BHIP has a low socio-economic development with low-income families and homes often with little infrastructure. It can be concluded that the BHIP still preserves typical rural characteristics, but already starting to show a small urban context.